Pengembangan Media Akar (Akidah Akhlak Reborn) Kelas XI di MA Al-Ihsan Kalikejambon - Ismah, Feniatul; Rohmah, Hidayatur (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
This research aims to determine the development of AKAR (Akidah Akhlak Reborn) media in the class XI moral aqidah subject at MA Al-Ihsan. AKAR media is learning media that is used for learning Aqidah Akhlak by using Power Point and Ispring Suite11 as an effort to increase student learning motivation. This development process produces AKAR media which is based on an Android application. AKAR media is said to be feasible after going through a validation process. This research uses R&D (Research and Development) development. The development model used is ADDIE which consists of 5 stages of analysis, design, development, implementation and evaluation.